Compartmental Analysis of Influenza A (H1N1) Virus using Induced SEIR Model - Kaur, Harpreet; Yadav, Atendra Singh (Journal of Neonatal Surgery, 2025)
Influenza A (H1N1) is highly contagious infectious disease. H1N1 has played a vital role in influenza pandemics from the deadly 1918 Spanish flu to milder but widespread 2009 swine flu pandemic. The 2009 H1N1 strain replaced older seasonal H1N1 strains and still circulate in current scenario. The improved induced SEIR mathematical model used to monitor H1N1 mutations to detect potential new pandemic threats through basic reproduction number, stability of the model. Also, MATLAB software used to represent the result graphically. The trends of several parts of the population that are suspectable, exposed, infectious, and recovered are examined based on the numerical solutions